2014
DOI: 10.4103/0976-237x.137932
|View full text |Cite
|
Sign up to set email alerts
|

Association of Transforming Growth Factor Alpha and Methylenetetrahydrofolate reductase gene variants with nonsyndromic cleft lip and palate in the Indian population

Abstract: Objectives:The aim was to evaluate the relationship of the K-primer variant of the transforming growth factor-alpha (TGF-α) gene and C677T variant of the methylenetetrahydrofolate reductase (MTHFR) gene with nonsyndromic cleft lip and palate (CL/P) in the Indian population.Setting and Sample Population:The study group consisted of DNA samples of 25 subjects with nonsyndromic CL with or without cleft palate and 25 unrelated controls, already existing in the Department of Orthodontics, D.A.P.M.R.V. Dental Colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The IRF6 gene, located on chromosome 1q32.3‐q41, is the most consistent finding for the genetic etiology of NSCLP (Leslie & Marazita, 2013; Lu et al., 2013). Several studies have indicated that the TGFA gene variant (the TGFA BamHI (rs11466297 A/C) and Vieira RsaI (rs3732248 C/T)) may also be associated with the increased risk of NSCLP (Desai et al., 2014; Ebadifar et al., 2015); however, other studies revealed some contradictory results (Lidral et al., 1997; Vieira, 2006). The possibility that interaction between IRF6 and TGFA genes contributes to the risk of NSCLP has also been reported (Letra et al., 2012; Lu et al., 2013) and it has been estimated that the contribution of the interaction between the two genes to be approximately 1% (Letra et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The IRF6 gene, located on chromosome 1q32.3‐q41, is the most consistent finding for the genetic etiology of NSCLP (Leslie & Marazita, 2013; Lu et al., 2013). Several studies have indicated that the TGFA gene variant (the TGFA BamHI (rs11466297 A/C) and Vieira RsaI (rs3732248 C/T)) may also be associated with the increased risk of NSCLP (Desai et al., 2014; Ebadifar et al., 2015); however, other studies revealed some contradictory results (Lidral et al., 1997; Vieira, 2006). The possibility that interaction between IRF6 and TGFA genes contributes to the risk of NSCLP has also been reported (Letra et al., 2012; Lu et al., 2013) and it has been estimated that the contribution of the interaction between the two genes to be approximately 1% (Letra et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between folate and craniofacial development has been establish in several vertebrate models (Carinci et al, 2019). Deficiency of nutritional folic acid has been hypothesized as a candidate factor of NSCLP and it is important to clear the association between NSCLP and MTHFR (Desai et al, 2014). For rs1801131A>C, the alteration of glutamine to alanine (Glu429Ala) in the regulatory domain leads to a 40% decrease in activity of MTHFR gene.…”
Section: Discussionmentioning
confidence: 99%